2017
DOI: 10.2196/resprot.8093
|View full text |Cite
|
Sign up to set email alerts
|

An eHealth Intervention to Promote Physical Activity and Social Network of Single, Chronically Impaired Older Adults: Adaptation of an Existing Intervention Using Intervention Mapping

Abstract: BackgroundEspecially for single older adults with chronic diseases, physical inactivity and a poor social network are regarded as serious threats to their health and independence. The Active Plus intervention is an automated computer-tailored eHealth intervention that has been proven effective to promote physical activity (PA) in the general population of adults older than 50 years.ObjectiveThe aim of this study was to report on the methods and results of the systematic adaptation of Active Plus to the wishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…Boekhout et al [34] adapted the intervention using the intervention mapping protocol for a chronically ill older adult (≥65 years) population. Based on a literature study, focus groups with the target population, and interviews with experts, it was concluded that the general determinants for PA in OACI were quite identical to general older adults.…”
Section: Intervention Groupmentioning
confidence: 99%
See 3 more Smart Citations
“…Boekhout et al [34] adapted the intervention using the intervention mapping protocol for a chronically ill older adult (≥65 years) population. Based on a literature study, focus groups with the target population, and interviews with experts, it was concluded that the general determinants for PA in OACI were quite identical to general older adults.…”
Section: Intervention Groupmentioning
confidence: 99%
“…In the present study, the intervention was tailored to two extra common chronic illnesses (neuromuscular and vascular disorders), and information on the risks of sedentary behaviour and benefits of PA for cognitive functioning were extended. A more detailed description of the intervention content and the process of adaption on the original and adapted Active Plus intervention can be found elsewhere [32,34,45].…”
Section: Intervention Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies used the IM protocol in the same manner as we did in this study. They decided to further build on the methodological choices made in the previously developed intervention by adjusting and improving the existing intervention for a new study population [71][72]. Methodological choices made in step two and three of the IM process of developing the original 'ikherstel'-intervention, as described in the IM article of Vonk Noordegraaf et al, are considered effective and therefore used again in this IM procedure [19].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%